What doesn't kill you makes you stronger? The impact of the 1918 Spanish flu epidemic on economic performance in Sweden - Martin Karlsson; Therese Nilsson; Stefan Pichler (Technische Universität Darmstadt, Department of Law and Economics, 2012)
We study the impact of the 1918 influenza pandemic on economic performance in Sweden. The pandemic was one of the severest and deadliest pandemics in human history, but it has hitherto received only scant attention in the economic literature - despite important implications for modern-day pandemics. In this paper, we exploit seemingly exogenous variation in incidence rates between Swedish regions to estimate the impact of the pandemic. Using difference-in-differences and high-quality administrative data from Sweden, we estimate the effects on earnings, capital returns and poverty. We find that the pandemic led to a significant increase in poverty rates. There is also relatively strong evidence that capital returns were negatively affected by the pandemic. On the other hand, we find robust evidence that the influenza had no discernible effect on earnings. This finding is surprising since it goes against most previous empirical studies as well as theoretical predictions.
Keywords: I18; J31; O40; 330; Spanish Flu; Difference-in-Differences; Infektionskrankheit; Epidemie; Einkommen; Kapitaleinkommen; Armut; Wirtschaftsgeschichte; Schätzung; Schweden